Reducción del drenaje profundo y la lixiviación de nitrógeno en rotaciones agrícolas con cultivos de cobertura - Portela, Silvina Isabel (2016)
Deep drainage and nitrogen leaching reduction in crop rotations with cover crops. Ecosystem water and nitrogen (N) fluxes can be altered by vegetation changes. The intensification of crop rotations with fall-winter cover crops (CC) reduces soil N and leaching risk during period of water excess. In this study we used filled-in lysimeters to evaluate the effect of including CC (oats and an oats+vetch mixture) in a soybean-maize rotation on deep drainage and N leaching during a rainy period. Rainfall was 732 and 562mm during 2014 and 2015 intercropping periods, and 817 and 705 mm during soybean and maize cropping periods, respectively. The introduction of CC reduced drainage during both intercropping periods (from 41 to 25% and from 22 to 9% of rainfall during the first and second intercropping periods, respectively) and during soybean cropping period (from 18 to 14% of rainfall). Drainage represented 14% of the rainfall of maize in both rotations. Mean drainage N-NO3¯ concentration was 6 and 15 mg/L for the rotation with and without CC, respectively, and the introduction of CC reduced leaching from 35 to 14 and from 17 to 3 kg N/ha during 2014 and 2015 intercropping periods, respectively, and from 36 to 3 and from 15 to 6 kg N/ha during soybean and maize cropping periods, respectively. These reductions, together with the additional N input from biological fixation of vetch, produced positive or close to neutral N balances while the rotation without CC produced negative balances. The inclusion of CC in the rotation not only improved internal N circulation. The reduction of drainage can translate into less groundwater recharge and the concomitant contribution to flooding regulation during rainy periods.